The sources of stress for junior table tennis players who attend the English national training centre - Bawden, M. A. K.; Chell, B. J.; Maynard, I. W. (Journal of Sports Sciences, 2006)
The sources of stress in elite athletes has been well documented in the academic literature (Jones, Swain & Cale, 1990). However, a new development in contemporary sport has been the emergence of national training centre's. When attending these centres many young sports performers are required to live and train within this highly intense environment. The young athlete is required to adapt to many life changes in order to reach the top level in their sport. These adaptations often involve many extra life stressors that contribute to the pressure that athletes perceive themselves to be under, in their quest to reach their potential. The present study interviewed players (n = 20) and coaches (n = 4) at the national table tennis academy in England. The players were asked to identify the sources of stress that negatively influence their performance. The coaches were also required to identify the sources of stress that they perceived the players to be under. The interview required the players and coaches to rank the sources of stress from most stressful to least stressful. The most commonly sighted sources were then placed into an overall hierarchy of sources of stress for both players and coaches. The ten sources of stress that were rated highest for players were : the critical eye of coaches, personal pressure, the constant need to win, living at the centre, other players perceptions of their ability, parents, the need to reach goals, playing players worse than themselves, the perception of people outside the centre and lack of freedom to socialise. The ten highest rated sources of stress as perceived by the coaches were : parents, coaches, lack of social activities, the need to win, the need to improve, evaluation from peers, selection, school, living away from home and the demands of training. The findings are discussed with reference to recommendations to help young players cope with stress when living, training and competing, whilst attending a national training centre.